2013
DOI: 10.1016/j.bbi.2012.11.003
|View full text |Cite
|
Sign up to set email alerts
|

PGE2 suppresses NK activity in vivo directly and through adrenal hormones: Effects that cannot be reflected by ex vivo assessment of NK cytotoxicity

Abstract: Surgery can suppress in vivo levels of NK cell cytotoxicity (NKCC) through various mechanisms, including catecholamine-, glucocorticoid (CORT)-, and prostaglandin (PG)-mediated responses. However, PGs are synthesized locally following tissue damage, driving proinflammatory and CORT responses, while their systemic levels are often unaffected. Thus, we herein studied the role of adrenal factors in mediating in vivo effects of PGs on NKCC, using adrenalectomized and sham-operated F344 rats subjected to surgery or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 47 publications
3
17
0
Order By: Relevance
“…Specifically, NK cells were shown to create immunological synapses with MADB106 cells in the lungs [33], marginating pulmonary NK cells were shown to efficiently kill MADB106 cells [31, 34, 35], and selective in vivo depletion of NK cells increased LTR and lung metastases by more than a hundred fold [27, 36-40]. Furthermore, we have shown that several stress paradigms, or the administration of stress-related factors (catecholamines and their agonists, and prostaglandins), can increase LTR in normal F344 rats, but not in NK-depleted rats, indicating that increased LTR in normal rats under these conditions reflects an in vivo suppression of NK-mediated activity [26, 27].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, NK cells were shown to create immunological synapses with MADB106 cells in the lungs [33], marginating pulmonary NK cells were shown to efficiently kill MADB106 cells [31, 34, 35], and selective in vivo depletion of NK cells increased LTR and lung metastases by more than a hundred fold [27, 36-40]. Furthermore, we have shown that several stress paradigms, or the administration of stress-related factors (catecholamines and their agonists, and prostaglandins), can increase LTR in normal F344 rats, but not in NK-depleted rats, indicating that increased LTR in normal rats under these conditions reflects an in vivo suppression of NK-mediated activity [26, 27].…”
Section: Methodsmentioning
confidence: 99%
“…For obvious reasons, in vitro studies alone are insufficient to conclude about the in vivo effects of these stress factors, and the ex-vivo approach may distort previous in vivo effects, as cytotoxicity is tested in vitro following the removal of all endogenous factors and in artificial conditions that do not simulate the in vivo milieu and its complex processes [30, 31]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, significant inconsistencies are prevalent between in vitro, ex-vivo , and in vivo findings regarding the nature and direction of the effects of specific stress hormones or stress paradigms on NK cell cytotoxicity (NKCC) [1]. For example, epinephrine was reported to suppress NKCC in vitro , both in human and animal blood [25], through activating NK cell adrenergic receptors and the consequent increase in intracellular cAMP levels [3]. However, ex-vivo human and animal studies reported contradictory results; many have demonstrated that administration of epinephrine, acute stress exposure, or exercise enhances NKCC [611], whereas some have reported suppression of NKCC [12–14].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies showed that prostaglandin-E2 (PGE2) can markedly suppresses NK activity [19, 29, 30], and in vivo studies reported deleterious impacts of PGs on resistance to cancer metastases [22], which is allegedly mediated through in vivo suppression of NK cells [31]. However, in a recent study in rats, we have provided evidence indicating that a direct in vivo suppressive effect of PGE2 on NKCC cannot be evident in an ex-vivo assessment of NKCC [5]…”
Section: Introductionmentioning
confidence: 99%